Representations of Europe at Times of Massive Migration Movements: A Qualitative Analysis of Greek-Cypriot Newspapers During the 2015 Refugee Crisis - Avraamidou, Maria; Kadianaki, Irini; Ioannou, Maria; Panagiotou, Elisavet (Javnost-The Public, 2019)
This paper presents a thematic analysis of a media criticism against the European Union (EU) during the so-called 2015 refugee crisis in one member-state, the Republic of Cyprus. Three inter-related negative representations of Europe were identified in the Greek-Cypriot newspapers studied at the time: inhuman Europe, fragmented Europe and Europe as perpetrator. All three represented Europe as unable or unwilling to deal with a crisis that Europe itself partly caused or reproduced. This media criticism focused on questioning Europe across pessimistic lines without offering or considering alternatives, thus served to reproduce the EU status quo. The paper discusses the implications of these findings in understanding the role of the media in the con-current skepticism towards EU in other member-states.